Formulation and Anti-Hair Fall Activities Serum of Keratin Extract from Chicken Feather Waste Combination with Aloe vera Extract - Walid Khalid K Al-yousif; Aldi Reynaldi Ramdani; Tiya Auliya Samsiah; Faizal Ardiansyah; Muhammad Nur Azzura Saraesa; Lela Khumaisah; Lela Yuningsih (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Hair loss is a disruption where hair falls out more than usual and suddenly, caused by genetics, age, and gender. A hair tonic or serum can usually be used to treat hairloss, but most products contain synthetic chemicals that worsen hair loss, so other alternatives are needed to overcome it with minimal side effects. Purpose: This study was conducted to determine the effectiveness of serum, the combination of keratin extract from chicken feather with Aloe vera extract, as a hair loss therapy. Methods: Chicken feather waste was added with Na2S, with 2 M HCl and then centrifuged. The keratin extract obtained was characterized using FTIR spectroscopy. Aloe vera extract was produced through maceration. The effectiveness of the anti-hair fall treatments was tested on New Zealand white rabbits using serum from 6% keratin extract (F1), 6% Aloe vera extract (F2), 6% Aloe vera gel (F3), and combinations of keratin and Aloe vera extracts in ratios of 1:1 (F4), 1:2 (F5), and 2:1 (F6), along with a normal control, and minoxidil (positive control). Result: The FTIR data reveals the characteristic peaks of keratin, specifically at 3292, 1645, 1533, 633, and 416 cm⁻¹. The highest activity results were achieved with F6, showing hair strength parameters rated at 4.6, surpassing the positive control rated at 2. In terms of hair growth, F3 demonstrated the best performance with a value of 31.43 mm. Conclusion: A serum formulated with keratin extract derived from chicken feather waste and Aloe vera extract shows a promising anti-hairloss treatment.